Pengaruh Tax Avoidance dan Return on Asset terhadap Nilai Perusahaan dengan Komisaris Independen sebagai Variabel Moderasi: Studi pada Perusahaan Sektor Industri yang Terdaftar di Bursa Efek Indonesia - Agistha Raissanaya; Hilda Mumtazah; Muhammad Amar Muzevy; Hexana Sri Lastanti (CV. Ulil Albab Corp, 2026)
This study aims to analyze the effect of tax avoidance and return on assets (ROA) on firm value with independent commissioners as a moderating variable in industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2023 period. Using a quantitative approach with 94 observations from 47 companies selected through purposive sampling, the analysis was conducted using a Random Effect Model (REM) with Moderated Regression Analysis (MRA) through EViews 9. The results show that tax avoidance has no significant effect on firm value, ROA has a positive and significant effect on firm value, independent commissioners are not proven to moderate the effect of tax avoidance on firm value, but independent commissioners are proven to significantly weaken the positive effect of ROA on firm value. These findings indicate that profitability is the dominant factor in forming firm value in the Indonesian industrial sector, while the effectiveness of independent commissioners as a governance mechanism still needs to be improved in terms of quality and actual independence to be able to optimally strengthen investor confidence.